Determinants of Risk Disclosure Level: Case of Indonesia - Akhir Syabani; Sylvia Veronica Siregar (The Indonesian Journal of Accounting Research, 2014)
Abstract: This research aims to examine the determinants of risk disclosure level of public listed firms in Indonesia Stock Exchange. Risk disclosure level is divided into three types, i.e., mandatory, voluntary, and total risk disclosure. The results show that generally firm size and product or service diversification has a positive effect on risk disclosure level, whereas geographic diversification positively affects only voluntary risk disclosure. Based on industry type, firms in certain sectors such as infrastructure, mining, agriculture, and property, have a higher level of risk disclosure than miscellaneous industries. Abstrak: This research aims to examine the determinants of risk disclosure level of public listed firms in Indonesia Stock Exchange. Risk disclosure level is divided into three types, i.e., mandatory, voluntary, and total risk disclosure. The results show that generally firm size and product or service diversification has a positive effect on risk disclosure level, whereas geographic diversification positively affects only voluntary risk disclosure. Based on industry type, firms in certain sectors such as infrastructure, mining, agriculture, and property, have a higher level of risk disclosure than miscellaneous industries.